2023
DOI: 10.1101/2023.02.22.529599
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA damage signaling inDrosophilamacrophages modulates systemic cytokine levels in response to oxidative stress

Abstract: Environmental factors, infection, or injury, cause oxidative stress in diverse tissues, resulting in immune activation and loss of tissue homeostasis. Effective stress response cascades, conserved from invertebrates to mammals, ensure reestablishment of homeostasis and tissue repair. Plasmatocytes, theDrosophilamacrophage-like cells, are thought to respond to oxidative stress by immune activation, however the signaling cascades involved in oxidative stress sensing and subsequent immune activation are yet to be… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Humoral immunity was also clearly activated in Gba1b mutants, but a large set of genetic manipulations found no evidence that the humoral immune system was involved in the development of neurological phenotypes. The most likely explanation for this is that the increased production of humoral factors is a consequence of macrophage activation [76][77][78]. Some previously published models of neurodegenerative disease have shown that excess production of humoral immune factors is sufficient to cause neurodegeneration [51,52,79,80] and in Drosophila, the detrimental effects of humoral activation were blocked by interfering with the upstream immune transcription factor Relish [51,52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Humoral immunity was also clearly activated in Gba1b mutants, but a large set of genetic manipulations found no evidence that the humoral immune system was involved in the development of neurological phenotypes. The most likely explanation for this is that the increased production of humoral factors is a consequence of macrophage activation [76][77][78]. Some previously published models of neurodegenerative disease have shown that excess production of humoral immune factors is sufficient to cause neurodegeneration [51,52,79,80] and in Drosophila, the detrimental effects of humoral activation were blocked by interfering with the upstream immune transcription factor Relish [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Humoral immunity was also clearly activated in Gba1b mutants, but a large set of genetic manipulations found no evidence that the humoral immune system was involved in the development of neurological phenotypes. The most likely explanation for this is that the increased production of humoral factors is a consequence of macrophage activation [7678].…”
Section: Discussionmentioning
confidence: 99%